2003
DOI: 10.1016/s0304-3959(03)00093-9
|View full text |Cite
|
Sign up to set email alerts
|

Innocuous jaw movements increase c-fos expression in trigeminal sensory nuclei produced by masseter muscle inflammation

Abstract: Muscle tenderness and pain during movements are prominent symptoms associated with persistent jaw muscle pain. However, there is virtually no information on how trigeminal neurons respond to jaw movements (JM) or muscle palpation in the presence of muscle tissue injury or myositis. In this study, we investigated the effects of innocuous JM in the presence of acute masseteric inflammation on postsynaptic responses in the trigeminal brainstem nuclei by examining the expression of c-fos. In one group of rats, uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 58 publications
5
22
0
Order By: Relevance
“…Despite these limitations, c-Fos is the most extensively studied marker available. In line with previous studies [33,85,86], we ob- served that inflammation induces hyperalgesia as well as c-Fos transcription and increases in the number of c-Fos immunoreactive cells in Laminae I and II in the dorsal horn (Fig. 6), and these changes were also detectable following PMN depletion.…”
Section: Discussionsupporting
confidence: 91%
“…Despite these limitations, c-Fos is the most extensively studied marker available. In line with previous studies [33,85,86], we ob- served that inflammation induces hyperalgesia as well as c-Fos transcription and increases in the number of c-Fos immunoreactive cells in Laminae I and II in the dorsal horn (Fig. 6), and these changes were also detectable following PMN depletion.…”
Section: Discussionsupporting
confidence: 91%
“…The group of animals pretreated with PBS in the masseter followed by MO injection exhibited a pattern of behavioral responses similar to that described for injection of MO alone (Ro et al, 2003; Fig. 3A).…”
Section: Resultssupporting
confidence: 64%
“…We have previously shown that algesic stimulation of the masseter muscle evokes ipsilateral hind-paw shaking responses in lightly anesthetized rats (Ro et al, 2003). Using the same behavioral paradigm we quantified the MO-induced hindpaw shaking responses in NBQX or vehicle treated rats by counting the number of shakes in 30-sec intervals.…”
Section: Methodsmentioning
confidence: 99%
“…1999), and masseter muscle inflammation (Imbe et al ., 1999; Ro et al ., 2003). These studies reveal an interesting pattern of trigeminal nociceptive neuronal activation (Fig.…”
Section: Vi/vc Neuronal Activation After Orofacial Injurymentioning
confidence: 99%